2003
DOI: 10.1053/jhep.2003.50289
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sclerosing Cholangitis in Children: A Long–Term Follow–Up Study

Abstract: Primary sclerosing cholangitis (PSC) is increasingly diagnosed in children and adolescents, but its long-term prognosis remains uncertain. The aim of this longitudinal, cohort study was to determine the long-term outcome of children with PSC. Fifty-two children with cholangiography-proven PSC (34 boys and 18 girls; mean age 13.8 ؎ 4.2 years; range, 1.5-19.6 years) who were seen at our institution over a 20-year period were followed-up for up to 16.7 years. Two thirds presented with symptoms and/or signs of PSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
224
7
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(265 citation statements)
references
References 25 publications
29
224
7
5
Order By: Relevance
“…In the study by Gregorio et al, 5 the presence of cholangiopathy was associated with a worse prognosis over the 16 years of follow-up; 4 of the 27 children with SC required liver transplant, whereas none of the 28 who lacked evidence of large duct biliary changes did. The survival analysis by Feldstein et al 38 of children with PSC revealed a survival disadvantage over an age-matched and gender-matched US population, regardless of the presence or absence of concomitant AIH. Pharmacological therapy did not seem to impact survival and long-term outcome in their longitudinal cohort assessment of 16 years.…”
Section: Discussionmentioning
confidence: 95%
“…In the study by Gregorio et al, 5 the presence of cholangiopathy was associated with a worse prognosis over the 16 years of follow-up; 4 of the 27 children with SC required liver transplant, whereas none of the 28 who lacked evidence of large duct biliary changes did. The survival analysis by Feldstein et al 38 of children with PSC revealed a survival disadvantage over an age-matched and gender-matched US population, regardless of the presence or absence of concomitant AIH. Pharmacological therapy did not seem to impact survival and long-term outcome in their longitudinal cohort assessment of 16 years.…”
Section: Discussionmentioning
confidence: 95%
“…Estella Alonso (Children's Memorial Hospital, Chicago, IL) addressed the special issues surrounding liver transplantation for children with PSC. PSC is an uncommon indication for liver transplantation in children, 19,20 being the cause for only 73 of 2219 (3.5%) children listed in the Studies of Pediatric Liver Transplantation (SPLIT) registry between 1995 and 2004. 157 Compared to children with other diagnoses, children with PSC were more likely to be male (64% vs. 47%: P ϭ .004), Caucasian and older in age (median ϭ 12.7 vs. 1.4 years), and were less likely to be hospitalized.…”
Section: Session Six Liver Transplantation For Pscmentioning
confidence: 99%
“…17,18 In children, PSC usually presents with nonspecific symptoms and pruritus, and rarely with jaundice. 11,13,[18][19][20][21][22] An autoimmune hepatitis-like presentation is common. 11,22 ERCP may demonstrate bile duct abnormalities in these children, 23 but their course is typical of autoimmune hepatitis, although with time, features of PSC become prominent.…”
mentioning
confidence: 99%
“…However, a quarter of the children with ASC, based on abnormal cholangiograms, had no histological features of bile duct involvement. Therefore, hepatologists should be very careful in making conclusions (34,35).…”
Section: Chronic Liver Disease In Older Childrenmentioning
confidence: 99%